APLIKASI KAIN BERBAHAN RAMI UNTUK PRODUK TEKSTIL KREATIF INTERIOR - Falah, Asep Miftahul (Jurusan Seni Rupa ISBI Bandung, 2023)
Fabrics made from ramie fiber have the potential to be developed as raw materials for creative textile products and their derivatives. The development of research on the application of ramie fiber based fabrics provides opportunities for the development of ramie fiber as a creative interior textile product. To create an interior textile product, a strategy is needed to carry out the exploration and experimentation process of making interior textile products from fabrics made from ramie fiber. This study aimed to obtain standard documents for analyzing the quality of hemp fiber fabrics and the production process for making prototype products, namely sunscreen, upholstery, lampshade, cushion, looper, coasters, and noreng. The application of ramie fiber-based fabrics will provide an alternative for the world of textiles as a raw material for textiles by carrying out various stages including material studies, shape studies, natural color studies, composition studies, and engineering studies. Qualitative research methods with exploratory and experimental approaches and data collection techniques are carried out using observation, interviews, and documentation. The results of research on the application of ramie fiber-based fabrics have excellent potential to be used as an alternative to interior creative textile products because they have properties that meet the requirements to be used as textile fibers. The results of this study will be a reference in the use of ramie fiber fabrics with standardized characters for the manufacture of superior works of interior creative textile products. Keywords: Fabrics, Natural Fibers, Ramie, Interior Textile ———————————————————————————— Kain berbahan serat rami berpotensi untuk dikembangkan sebagai bahan baku untuk produk kreatif tekstil dan turunannya. Perkembangan riset tentang aplikasi kain berbahan serat rami memberikan peluang untuk pengembangan serat rami sebagai produk tekstil kreatif interior. Untuk menciptakan sebuah produk tekstil interior, perlu strategi untuk melakukan proses eksplorasi dan eksperimentasi pembuatan produk tekstil interior dari kain berbahan serat rami. Tujuan penelitian ini adalah mendapatkan dokumen standard untuk analisis kualitas kain berbahan serat rami dan proses produksi pembuatan produk prototype yaitu sunscreen, upholstery, kap lampu, cushion, looper, coaster, dan noreng. Aplikasi kain berbahan serat rami serat akan memberi alternatif untuk dunia tekstil sebagai bahan baku tekstil dengan melakukan berbagai tahapan diantaranya studi material, studi bentuk, studi warna alami, studi komposisi, dan studi teknik. Metode penelitian kualitatif dengan pendekatan eksplorasi dan ekperimentasi, teknik pengumpulan data dilakukan dengan cara observasi, wawancara, dan dokumentasi. Hasil penelitian aplikasi kain berbahan serat rami memiliki potensi yang sangat baik untuk dijadikan alternatif produk tekstil kreatif interior, karena mempunyai sifat-sifat yang dapat memenuhi persyaratan untuk dijadikan serat tekstil. Hasil penelitian ini akan menjadi acuan dalam penggunaan kain berbahan serat rami dengan karakter terstandar untuk pembuatan karya unggulan produk tekstil kreatif interior. Kata Kunci: Kain, Serat Alami, Rami, Tekstil Interior